Identification of Salmonella Sp Bacterial Contamination in Broiler Chicken at Pon Market, Jombang Regency: Identifikasi Cemaran Bakteri Salmonella Sp Pada Daging Ayam Broiler Di Pasar Pon Kabupaten Jombang - Rizki, Ramadhani Putri; Arifin, M. Zainul; Aini, Inayatul (Universitas Muhammadiyah Sidoarjo, 2022)
Broiler chicken meat is a type of meat that is much favored by the public because of its high nutritional content with good taste and relatively low price. However, the high protein and water content causes this meat to be easily contaminated by microbes, one of which is Salmonella sp. Salmonella sp can cause Salmonellosis, in humans salmonellosis is transmitted through food because it is undercooked during cooking so that Salmonella sp bacteria enter the body. To determine the presence of Salmonella sp bacteria in broiler chicken meat in the pound market, Jombang district. The design of this research is descriptive. The sample of this research was obtained from 8 chicken traders with total sampling technique. The variables in this study were salmonella sp bacteria in broiler chicken meat. This research method uses the scratch method. The results of the 8 samples of broiler chicken examined were found to be half(50%) contaminated with Salmonella sp and half(50%) not contaminated with Salmonella sp. From this study it was found that half of the population of broiler chicken meat sold in the pound market was contaminated with Salmonella sp.